Managing Director's Consolidated Multilateral Surveillance Report to the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2012)
After suffering a major setback, global prospects are gradually strengthening again. Improved activity in the United States and better policies in the euro area in response to the deepening economic crisis there have reduced the immediate threat of a sharp global slowdown. Weak recovery is likely to resume in the major advanced economies, and activity should remain relatively solid in emerging market and developing economies.